Fast detection of leaf pigments and isoprenoids for ecophysiological studies, plant phenotyping and validating remote‐sensing of vegetation. Issue 4 (14th October 2016) - Junker, Laura V.; Ensminger, Ingo
Abstract : Rapid developments in remote‐sensing of vegetation and high‐throughput precision plant phenotyping promise a range of real‐life applications using leaf optical properties for non‐destructive assessment of plant performance. Use of leaf optical properties for assessing plant performance requires the ability to use photosynthetic pigments as proxies for physiological properties and the ability to detect these pigments fast, reliably and at low cost. We describe a simple and cost‐effective protocol for the rapid analysis of chlorophylls, carotenoids and tocopherols using high‐performance liquid chromatography (HPLC). Many existing methods are based on the expensive solvent acetonitrile, take a long time or do not include lutein epoxide and α‐carotene. We aimed to develop an HPLC method which separates all major chlorophylls and carotenoids as well as lutein epoxide, α‐carotene and α‐tocopherol. Using a C30 ‐column and a mobile phase with a gradient of methanol, methyl‐tert‐butyl‐ether (MTBE) and water, our method separates the above pigments and isoprenoids within 28 min. The broad applicability of our method is demonstrated using samples from various plant species and tissue types, e.g. leaves of Arabidopsis and avocado plants, several deciduous and conifer tree species, various crops, stems of parasitic dodder, fruit of tomato, roots of carrots and Chlorella algae. In comparison to previous methods, our method is very affordable, fast and versatile and can be used to analyze all major photosynthetic pigments that contribute to changes in leaf optical properties and which are of interest in most ecophysiological studies.